Investigation into the behaviour of aluminium and steel under melt/freeze cyclic conditions. (June 2018) - Jacob, Rhys; Sibley, Alexander; Belusko, Martin; Liu, Ming; Quinton, Jamie; Andersson, Gunter
Highlights: The performance of aluminium in contact with carbon and stainless steels over 100 cycles is measured. Initial results suggest that some degradation in melting/freezing onset temperature and phase change duration occurs. Significant degradation of carbon steel can be seen on both the outer and inner surface of the crucible. While degradation of the stainless steel surfaces occurred, it was to a much less extent. EDS shows that an interface between aluminium and steel did not readily occur under the test conditions. Abstract: In the current study aluminium has been cycled around its melting temperature (660 °C) in stainless and carbon steel crucibles. The interaction between the crucibles and aluminium have been studied using scanning electron microscopy (SEM) and auger electron spectroscopy (AES), while the phase change behaviour of the aluminium has also been studied. It could be seen that after 10 cycles a black carbonaceous layer forms on the surface of the crucibles preventing aluminium and steel interaction. After 60 cycles this layer is still present on the stainless steel samples but has been removed, from the carbon steel surface, most likely from thermal cycling. This layer has resulted in much fewer instances of aluminium penetration into the stainless steel over the carbon steel. Similar results are seen for the 100 cycle samples. In instances where aluminium has been in contact with the steel, Fe2 Al5 and FeAl3 have been present. It is suggested that the presence of these products is the likely cause of the change in aluminium phase change performance. Overall, it was found that under the conditions present in the study that stainless steel suffered from far less aluminium intrusion than the carbon steel samples. It was hypothesised that the carbon layer found on the surface of the samples largely prevented any aluminium interaction, preventing the loss of stainless steel at the interface. In contrast to the mild steel samples, the carbon layer was found to adhere to the stainless steel much more effectively, preventing aluminium and steel interaction. The potential for this carbon layer to act as a barrier to corrosion between stainless steel and aluminium warrants further investigation.